2015
DOI: 10.1177/0161734614568532
|View full text |Cite
|
Sign up to set email alerts
|

Shear Wave Wavefront Mapping Using Ultrasound Color Flow Imaging

Abstract: A wavefront reconstruction method for a continuous shear wave is proposed. The method uses ultrasound color flow imaging (CFI) to detect the shear wave's wavefront. When the shear wave vibration frequency satisfies the required frequency condition and the displacement amplitude satisfies the displacement amplitude condition, zero and maximum flow velocities appear at the shear wave vibration phases of zero and π rad, respectively. These specific flow velocities produce the shear wave's wavefront map in CFI. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…Our novel estimation method for shear wave elastography was implemented using ultrasound scanners (Xario SSA-660A, Toshiba, Japan). The shear wave imaging method was previously described; quantitative evaluation confirmed a good correlation between the small displacement estimation method and shear wave velocity measured using our new method 15,33,34 . Notably, shear wave velocity is derived from stiffness by assuming that shear viscosity is negligible.…”
Section: Methodsmentioning
confidence: 62%
See 2 more Smart Citations
“…Our novel estimation method for shear wave elastography was implemented using ultrasound scanners (Xario SSA-660A, Toshiba, Japan). The shear wave imaging method was previously described; quantitative evaluation confirmed a good correlation between the small displacement estimation method and shear wave velocity measured using our new method 15,33,34 . Notably, shear wave velocity is derived from stiffness by assuming that shear viscosity is negligible.…”
Section: Methodsmentioning
confidence: 62%
“…Powdered agar (g) Sterilized milk (ml) www.nature.com/scientificreports/ showed that shear wave velocity measurements in phantom gels, supraclavicular muscles, and trapezius muscles acquired using the new method were consistent with those acquired by means of other instruments 15,33,34,51,52 .…”
Section: Concentration (%)mentioning
confidence: 70%
See 1 more Smart Citation
“…The shear wave was produced using a custom-made vibrator with a vibration amplitude of approximately 600 µm under an applied voltage of approximately 1 V. The resultant shear wave frequency was 276.5 Hz, which satisfies k = 1 of the shear wave frequency condition. 10 The vibrator head and the ultrasonic probe were aligned to enable perpendicular propagation of the shear wave wavefront. Figure 9 shows the four consecutive CFIs recorded using the breast phantom; these images were obtained from the area within the yellow square on the right side of Figure 8.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4] Several methods for SWEI have been proposed, including strain elastography and ultrasound push pulse-based shear wave elastography. [5][6][7][8][9][10][11] Strain elastography has a number of advantages over other elastography methods, including quick and easy image acquisition. However, because quantification using this method is difficult, relative evaluations, such as the Tsukuba-score for thyroid nodules, are generally employed.…”
Section: Introductionmentioning
confidence: 99%